2020
DOI: 10.1177/0959683620941137
|View full text |Cite
|
Sign up to set email alerts
|

The transformation of cropping patterns from Late Neolithic to Early Iron Age (5900–2100 BP) in the Gansu–Qinghai region of northwest China

Abstract: The Gansu–Qinghai region lies in the key position for trans-Eurasian cultural exchange, and hence investigations of the history of agricultural development in this region are significant for understanding the spatiotemporal evolution of prehistoric crop dispersal in Eurasia. However, systematic archaeobotanical studies concerning the history of the development of prehistoric agriculture in this area are scarce. Here, based on archaeobotanical analysis and radiocarbon dating at the Jinchankou site, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Prior to the spread into the Plateau, barley agriculture was practiced by Late Neolithic and Early Bronze Age populations in the Gansu-Qinghai region, such as those associated with the Qijia culture (ca. 2300–1800 BCE) 19 , 20 . This cline may also have been established or reinforced by later historical events, such as the expansion of the Tibetan empire since the 7th century CE, or by a prolonged process of gene flow between nearby populations in an isolation-by-distance manner that did not involve long-range migrations.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the spread into the Plateau, barley agriculture was practiced by Late Neolithic and Early Bronze Age populations in the Gansu-Qinghai region, such as those associated with the Qijia culture (ca. 2300–1800 BCE) 19 , 20 . This cline may also have been established or reinforced by later historical events, such as the expansion of the Tibetan empire since the 7th century CE, or by a prolonged process of gene flow between nearby populations in an isolation-by-distance manner that did not involve long-range migrations.…”
Section: Introductionmentioning
confidence: 99%
“…3, orange dots), and the third phase (3.5–2 ka) is represented by Xindian, Kayue, and Nuomuhong culture sites (Fig. 3, purple dots) (Dong et al, 2021; Ren et al, 2021). This time lag relates to the fact that sheep and cattle appeared later in the catchment area of the STP.…”
Section: Discussionmentioning
confidence: 99%
“…5.2 How millet farming groups responded to climate change in the mid-lower Hulu River Valley during ~4,800-3,900 BP Climate changes, especially rapid and extreme climate events, are proposed as an important factor for cultural evolution and the transformation of subsistence strategies in different corners of Eurasia during the Neolithic periods (Staubwasser et al, 2003;Wu and Liu, 2004;Weiss, 2017;Park et al, 2019;Ran and Chen, 2019;, including northwest China (Dong et al, 2012;Zhou et al, 2016;Cao and Dong, 2020;Ren et al, 2021). While social resilience to climate change gradually increased with innovations and the dispersal of agricultural techniques across Eurasia, Neolithic groups could adopt different strategies to cope with climate change (Yang et al, 2019;Yang et al, 2020;Dong et al, 2021;Tao et al, 2022).…”
Section: Human Planting Strategies In the Midlower Hulu River Valley ...mentioning
confidence: 99%
“…This indicates that millet farming groups substantially expanded in the area under a relatively cold-dry climate. Previous studies have suggested that Neolithic groups might have successfully adapted to climate events in different ways, including the alteration of cropping patterns (Pokharia et al, 2017;Chen et al, 2020;Li R et al, 2020), the improvement of field management (Masi et al, 2014;Ren et al, 2021) and the enlargement of the cultivated land area (An et al, 2021). Nevertheless, differences in planting strategies between the Lower Changshan period and the Qijia period in the MLHRV remains unclear due to the absence of systematic archaeobotanical studies.…”
Section: Introductionmentioning
confidence: 99%